CORRELATION OF BLOOD PRESSURE CHANGES IN RESPONSE TO SUSTAINED ISOMETRIC EXERCISE WITH RESPECT TO BODY MASS INDEX IN ADULTS OF HASSAN, KARNATAKA - Divyashree; MAMATHA, CHIKKADANUR NINGANNA; VEENA, HOSALLI CHANDREGOWDA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The prevalence of obesity is increasing among Indians. Body mass index (BMI) marker of obesity might affect the pressure response to exercise. The present study was undertaken to correlate the blood pressure response to isometric exercise with BMI among males and females. Method: This cross-sectional study comprised 100 male and 100 female subjects 20–40 years old depending on the set inclusion and exclusion criteria. Anthropometric parameters weight, height measured, and blood pressure recorded before exercise. Then subjects were asked to execute isometric hand grip strength at 30% of their maximum voluntary contraction and blood pressure was recorded before the release hand grip. Data were analyzed by the mean and standard deviation of systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP). An unpaired t-test was to compare blood pressure parameter changes in isometric exercise between males and females. Pearson’s coefficient of correlation test was used to correlate blood pressure response with BMI in males and females. Statistical significance was fixed at a p<0.05. Result: In both males and females, SBP, DBP, and MAP were increased after exercise. There is a significant positive correlation between DBP response to isometric exercise with BMI among males and females. Conclusion: This knowledge about the variation of blood pressure response to isometric exercise with BMI is essential for the physicians to educate overweight and obese individuals to adopt a healthy lifestyle to prevent future cardiovascular morbidity.